A high-strength refractory material for incinerator lining and preparation method thereof

By using combined materials such as phosphate water reducers and composite powders, the problem of insufficient wear resistance of traditional incinerator lining materials in high temperature and corrosion environments is solved, and a high strength and high thermal stability in incinerator lining materials are achieved.

CN118955153BActive Publication Date: 2025-03-25JIANGSU GUOHAO REFRACTORY TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311159237.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-09
Publication Date
2025-03-25
Estimated Expiration
2043-09-09

AI Technical Summary

Technical Problem

The traditional incinerator lining materials have poor wear resistance in high temperature and corrosion environments, and the strength and high temperature stability of refractory castables still need to be improved.

Method used

Combined materials such as phosphate water reducers and composite powders are used to form high-strength refractory materials through the preparation of phosphate monomers, the addition of polypropylene fibers, and the use of lanthanum zirconate and yttrioxide.

Benefits of technology

It improves the high strength and high thermal stability of the incinerator lining material, enhances the material's wear resistance and durability, and is suitable for the preparation of incinerator lining.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of refractory materials, specifically to a high-strength refractory material for an incinerator lining and a preparation method thereof. The present invention reacts L-2-amino-3-hydroxybutyric acid-3-phosphate with 2-acrylamide-2-methylpropanesulfonic acid to generate a phosphate monomer, and uses it as a third monomer to modify a polycarboxylic acid water reducer to obtain a phosphate type water reducer; a lanthanum zirconate powder is prepared by a coprecipitation method, and calcium carbonate is loaded on its outer layer to obtain a composite powder to improve heat resistance; the composite powder is mixed with high-aluminum aggregate, silicon carbide powder, α-alumina powder, silicon dioxide particles, silicate cement, spherical asphalt, phosphate type water reducer, polypropylene fiber, and yttrium trioxide powder to obtain a high-strength, high-temperature resistant refractory material that can be used to prepare an incinerator lining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a high-strength refractory material for an incinerator lining and a preparation method thereof. Background Art

[0002] Incinerator is an environmental protection equipment widely used in the treatment of industrial waste, domestic waste and medical waste. It consists of pre-treatment system, incineration system, smoke biochemical dust removal system and auxiliary ignition system. The garbage is burned at high temperature in the incineration furnace to become waste gas. The waste gas enters the secondary combustion chamber and is discharged into the atmosphere after complete combustion and dust removal. It can not only achieve harmless treatment, but also effectively reduce the volume of waste, reduce the content of toxic substances and recover energy. In order to achieve this goal, the interior of the incinerator needs to have the characteristics of high strength, wear resistance, high temperature resistance and chemical corrosion resistance. Therefore, the refractory material used for the lining of the incinerator is very important.

[0003] The traditional lining materials of incinerators are mainly refractory bricks, including magnesia bricks, high alumina bricks and siliceous bricks. These bricks have good refractory properties and mechanical strength, but their wear resistance in high temperature and corrosive environments is relatively poor. Refractory castables are a type of amorphous refractory material, mainly composed of refractory aggregates, binders and additives. Compared with refractory bricks, refractory castables have better construction performance, higher corrosion resistance and lower temperature drop rate. However, the strength and high temperature stability of refractory castables still need to be improved. Summary of the invention

[0004] The object of the present invention is to provide a high-strength refractory material for incinerator lining and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength refractory material for incinerator lining and a preparation method thereof, comprising the following steps:

[0006] Step 1: Disperse 2-acrylamide-2-methylpropanesulfonic acid and L-2-amino-3-hydroxybutyric acid-3-phosphate in a sodium chloride solution, filter after the reaction is completed, and vacuum dry to obtain a phosphate monomer;

[0007] Step 2: Mixing acrylic acid with pure water to obtain solution A; mixing 3-mercaptopropionic acid, L-ascorbic acid with pure water to obtain solution B; adding isopentanol polyoxyethylene ether and phosphate monomer into pure water, heating to dissolve, adding hydrogen peroxide with stirring, and simultaneously dropping solution A and solution B to obtain a reaction solution; keeping the temperature for reaction, cooling and adjusting the pH value to 6-7 to obtain a phosphate type water reducer;

[0008] Step 3: lanthanum nitrate, zirconium oxychloride and pure water are mixed to obtain a precursor solution; sodium hydroxide is used to maintain the pH of the system to 9-10 for reaction, centrifugation is performed, and drying is performed to obtain a core powder; the core powder is dispersed in pure water, sodium dodecylbenzene sulfonate is added and stirred, and a calcium chloride solution is added dropwise. After the addition is completed, a sodium carbonate solution is added to obtain a suspension, and the suspension is reacted, filtered, dried, calcined, and crushed to obtain a composite powder;

[0009] Step 4: Mix high-alumina aggregate, silicon carbide powder, α-alumina powder, silica particles, silicate cement, spherical asphalt, phosphate-type water reducer, polypropylene fiber, composite powder, and yttrium trioxide powder to obtain the high-strength refractory material.

[0010] Furthermore, in step 1, the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to L-2-amino-3-hydroxybutyric acid-3-phosphate is (1.1-1.4):1.

[0011] Furthermore, in step 1, the reaction is carried out under a nitrogen environment, the reaction temperature is 5 to 15° C., and the reaction time is 1 to 2 h.

[0012] Furthermore, in step 2, the contents of each component in solution A are, by weight, 5 to 5.5 parts of acrylic acid and 2 to 2.5 parts of pure water; the contents of each component in solution B are, by weight, 1.8 to 2 parts of 3-mercaptopropionic acid, 1.2 to 1.5 parts of L-ascorbic acid, and 50 to 60 parts of pure water.

[0013] Furthermore, in step 2, the contents of the components in the reaction solution are, by weight, 63 to 68 parts of isopentanol polyoxyethylene ether, 3.7 to 4.5 parts of phosphate monomers, 20 to 25 parts of pure water, 0.36 to 0.4 parts of hydrogen peroxide, 5.8 to 6.2 parts of solution A, and 6 to 6.4 parts of solution B.

[0014] Furthermore, in step 3, in the precursor solution, La 3+ With Zr 4+ The molar ratio is (1~1.2):1.

[0015] Furthermore, in step 3, the contents of the components in the suspension are, by weight, 5 to 10 parts of core powder, 1 to 2 parts of sodium dodecylbenzene sulfonate, 30 to 50 parts of pure water, 13 to 17 parts of calcium chloride solution, and 15 to 22 parts of sodium carbonate solution.

[0016] Furthermore, in step 4, the contents of each component in the high-strength refractory material are, by weight, 62 to 67 parts of high-alumina aggregate, 13 to 22 parts of silicon carbide powder, 4 to 8 parts of α-alumina powder, 3 to 5 parts of silica particles, 2 to 3 parts of silicate cement, 2 to 3 parts of spherical asphalt, 1 to 2 parts of phosphate-type water reducer, 0.01 to 0.2 parts of polypropylene fiber, 3 to 7 parts of composite powder, and 0.5 to 1.5 parts of yttrium oxide powder.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: the refractory material prepared by the present invention has high strength and high thermal stability, and can be used to prepare the lining of an incinerator.

[0018] A phosphoric acid type water reducer is prepared by a phosphoric acid ester monomer, wherein the phosphoric acid ester monomer uses L-2-amino-3-hydroxybutyric acid-3-phosphate and 2-acrylamide-2-methylpropane sulfonic acid as raw materials. During the preparation process, since the reactant 2-acrylamide-2-methylpropane sulfonic acid is very easy to self-polymerize after being dissolved in water, the reaction is carried out in a sodium salt solution and a nitrogen environment, and the reaction temperature is controlled between 5 and 15°C; an excess of 2-acrylamide-2-methylpropane sulfonic acid is added to allow the reactant L-2-amino-3-hydroxybutyric acid-3-phosphate to fully react, and the unreacted 2-acrylamide-2-methylpropane sulfonic acid has excellent water solubility and can be separated from the product phosphoric acid ester monomer by filtering. The phosphoric acid ester type water reducer obtained by the reaction of the phosphoric acid ester monomer, isopentanol polyoxyethylene ether and acrylic acid has better performance than conventional polycarboxylic acid water reducers, hydrolyzes to produce phosphoric acid groups during the application process, has a stronger adsorption effect on calcium ions in cement, can form a stable structure on the cement surface, and improves the strength after hardening.

[0019] After adding polypropylene fiber, as the temperature rises, polypropylene begins to soften, shrink, melt, and finally form pores and carbonize, forming tiny network pores inside the refractory material, opening up water and gas channels, reducing internal stress, preventing bursting, and increasing the service life of the refractory material.

[0020] Lanthanum zirconate has high temperature stability, and can improve high temperature resistance after being added, but lanthanum zirconate itself has poor toughness, and direct addition will cause adverse effects such as decreased strength and poor durability of refractory materials. The present invention adds a composite powder with lanthanum zirconate as the core powder and calcium carbonate as the shell; at the same time, yttrium trioxide with a good sintering aid effect is added as a sintering aid. Yttrium trioxide can reduce the eutectic point of materials such as silicon dioxide, magnesium oxide, and aluminum oxide to form a low eutectic phase. The generation of the liquid phase changes the sintering process originally dominated by solid phase reaction into a process in which the solid phase and the liquid phase participate together, accelerating the movement between particles and promoting mass transfer; during the baking process, when the temperature reaches above 900°C, the calcium carbonate in the shell of the composite powder is decomposed into calcium oxide and carbon dioxide by heat, and the discharge of carbon dioxide forms pores around the lanthanum zirconate; the low eutectic phase penetrates into the pore space in liquid form, and forms a crystalline coating around the lanthanum zirconate to fill the pores, reduce the apparent porosity, and thus improve the density of the material. Lanthanum zirconate has a grain boundary strengthening effect and can further combine with the generated crystal phase coating. The coating has higher strength and thermal stability, which can effectively protect lanthanum zirconate from damage under external forces, making up for the shortcomings of lanthanum zirconate. In addition, the composite powder shell calcium carbonate contains functional groups such as hydroxyl and carboxyl groups, which can form chemical bonds or ionic bonds with the phosphate groups of the phosphate-type water reducer and form a thin film on the surface of the composite powder, thereby changing its surface properties and facilitating the uniform dispersion of the composite powder in the refractory material. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The main materials and their sources in the following embodiments are as follows: isopentanol polyoxyethylene ether TPEG-2400 comes from Keward Chemical, high alumina aggregate comes from Shengyuan refractory insulation materials, with a particle size of 3 to 5 mm; silicon carbide micropowder comes from Shunhengshun wear-resistant materials, item number SHS-HTHG-04; α-alumina powder comes from Tuorui fine grinding materials, model TR-2, α-alumina content ≥95%; silicon dioxide particles come from Zhongke Yannuo, with a particle size of 1 to 3 mm; silicate cement comes from P.O52.5R silicate cement from Hongye Special Cement Company; spherical asphalt comes from Jinhuo high temperature materials, with a particle size of 0.2 to 1 mm; polypropylene fiber comes from Kaibisheng new building materials, item number 1012; yttrium trioxide powder comes from Jinlei Nanomaterials, item number JL-Y2O3.

[0023] Example 1

[0024] Step 1: 1.1 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 5° C. for 1 h in a nitrogen environment, filtered, and vacuum dried to obtain a phosphate monomer;

[0025] Step 2: 5g of acrylic acid and 2g of pure water were mixed in a weight ratio to obtain solution A; 1.8g of 3-mercaptopropionic acid, 1.2g of L-ascorbic acid, and 50g of pure water were mixed to obtain solution B; 63g of isopentanol polyoxyethylene ether and 3.7g of phosphate monomer were added to 20g of pure water, heated to 50°C, and 0.38g of hydrogen peroxide was added after dissolution. After stirring for 15min, 5.8g of solution A and 6g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0026] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1:1; use sodium hydroxide to maintain the pH of the system to 9, stir and stand for 1 hour, centrifuge and dry to obtain the core powder; take 5g of the core powder and disperse it in 30g of pure water, add 1g of sodium dodecylbenzene sulfonate, stir for 30min, add 13g of calcium chloride solution dropwise, add 15g of sodium carbonate solution after the addition is completed, obtain a suspension, stir and react for 1h, filter, dry, calcine, and grind to obtain a composite powder;

[0027] Step 4: 62 kg of high-alumina aggregate, 13 kg of silicon carbide powder, 4 kg of α-alumina powder, 3 kg of silica particles, 2 kg of silicate cement, 2 kg of spherical asphalt, 1 kg of phosphate-type water reducer, 0.1 kg of polypropylene fiber, 3 kg of composite powder, and 0.5 kg of yttrium trioxide powder are mixed to obtain the high-strength refractory material.

[0028] Example 2

[0029] Step 1: 1.1 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. in a nitrogen environment for 1.5 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0030] Step 2: 5.1g of acrylic acid and 2g of pure water were mixed in a weight ratio to obtain solution A; 1.9g of 3-mercaptopropionic acid, 1.25g of L-ascorbic acid, and 50g of pure water were mixed to obtain solution B; 62g of isopentanol polyoxyethylene ether and 3.75g of phosphate monomer were added to 20g of pure water, heated to 50°C, and 0.36g of hydrogen peroxide was added after dissolution. After stirring for 15min, 5.8g of solution A and 6.3g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0031] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.05:1; use sodium hydroxide to maintain the pH of the system to 10, stir and let stand for 1 hour, centrifuge and dry to obtain the core powder; take 6.5g of the core powder and disperse it in 35g of pure water, add 1.5g of sodium dodecylbenzene sulfonate, stir for 30min, add 17g of calcium chloride solution dropwise, add 15g of sodium carbonate solution after the addition is complete, obtain a suspension, stir and react for 2h, filter, dry, calcine, and grind to obtain a composite powder;

[0032] Step 4: 63 kg of high-alumina aggregate, 15 kg of silicon carbide powder, 5 kg of α-alumina powder, 3.8 kg of silica particles, 2.4 kg of silicate cement, 2.1 kg of spherical asphalt, 2 kg of phosphate-type water reducer, 0.13 kg of polypropylene fiber, 3.8 kg of composite powder, and 0.6 kg of yttrium trioxide powder are mixed to obtain the high-strength refractory material.

[0033] Example 3

[0034] Step 1: 1.19 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 10° C. in a nitrogen environment for 1.5 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0035] Step 2: 5.2g of acrylic acid and 2.3g of pure water were mixed in a weight ratio to obtain solution A; 1.86g of 3-mercaptopropionic acid, 1.34g of L-ascorbic acid, and 58g of pure water were mixed to obtain solution B; 65g of isopentanol polyoxyethylene ether and 3.9g of phosphate monomer were added to 22g of pure water, heated to 55°C, and 0.37g of hydrogen peroxide was added after dissolution. After stirring for 15min, 5.94g of solution A and 6.15g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0036] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.05:1; use sodium hydroxide to maintain the pH of the system to 10, stir and stand for 1 hour, centrifuge and dry to obtain the core powder; take 7.5g of the core powder and disperse it in 45g of pure water, add 1.45g of sodium dodecylbenzene sulfonate, stir for 30min, add 14g of calcium chloride solution dropwise, add 18g of sodium carbonate solution after the addition is completed, obtain a suspension, stir and react for 1.5h, filter, dry, calcine, and grind to obtain a composite powder;

[0037] Step 4: Mix 65kg of high-alumina aggregate, 17kg of silicon carbide powder, 6kg of α-alumina powder, 4.9kg of silica particles, 2.5kg of silicate cement, 2.7kg of spherical asphalt, 1.5kg of phosphate-type water reducer, 0.1kg of polypropylene fiber, 4.8kg of composite powder, and 0.7kg of yttrium trioxide powder to obtain the high-strength refractory material.

[0038] Example 4

[0039] Step 1: 1.24 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. for 2 h in a nitrogen environment, filtered, and vacuum dried to obtain a phosphate monomer;

[0040] Step 2: 5.3g of acrylic acid and 2.28g of pure water were mixed in a weight ratio to obtain solution A; 1.83g of 3-mercaptopropionic acid, 1.41g of L-ascorbic acid, and 50g of pure water were mixed to obtain solution B; 67g of isopentanol polyoxyethylene ether and 4g of phosphate monomer were added to 22g of pure water, heated to 50°C, and 0.39g of hydrogen peroxide was added after dissolution. After stirring for 15min, 6.1g of solution A and 6.23g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0041] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.15:1; use sodium hydroxide to maintain the pH of the system to 9.5, stir and stand for 1h, centrifuge and dry to obtain the inner core powder; take 8.7g inner core powder and disperse it in 45g pure water, add 1.6g sodium dodecylbenzene sulfonate, stir for 30min, add 15g calcium chloride solution dropwise, add 20.3g sodium carbonate solution after the addition is complete, obtain a suspension, stir and react for 2h, filter, dry, calcine, and grind to obtain a composite powder;

[0042] Step 4: 66 kg of high-alumina aggregate, 18.6 kg of silicon carbide powder, 7.5 kg of α-alumina powder, 4.3 kg of silica particles, 2.8 kg of silicate cement, 2.8 kg of spherical asphalt, 1.76 kg of phosphate-type water reducer, 0.2 kg of polypropylene fiber, 5.8 kg of composite powder, and 0.8 kg of yttrium trioxide powder are mixed to obtain the high-strength refractory material.

[0043] Example 5

[0044] Step 1: 1.35 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. in a nitrogen environment for 2 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0045] Step 2: 5.36g of acrylic acid and 2.3g of pure water were mixed in a weight ratio to obtain solution A; 1.9g of 3-mercaptopropionic acid, 1.5g of L-ascorbic acid, and 60g of pure water were mixed to obtain solution B; 67g of isopentanol polyoxyethylene ether and 4.18g of phosphate monomer were added to 23g of pure water, heated to 55°C, and 0.38g of hydrogen peroxide was added after dissolution. After stirring for 15min, 6.05g of solution A and 6.25g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0046] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1:1; use sodium hydroxide to maintain the pH of the system to 9.5, stir and stand for 1 hour, centrifuge and dry to obtain the core powder; take 8g of the core powder and disperse it in 45g of pure water, add 1.8g of sodium dodecylbenzene sulfonate, stir for 30min, add 16.5g of calcium chloride solution dropwise, add 21g of sodium carbonate solution after the addition is complete, obtain a suspension, stir and react for 1.5h, filter, dry, calcine, and grind to obtain a composite powder;

[0047] Step 4: 66 kg of high-alumina aggregate, 20 kg of silicon carbide powder, 8 kg of α-alumina powder, 4 kg of silica particles, 2.8 kg of silicate cement, 2.8 kg of spherical asphalt, 2 kg of phosphate ester water reducer, 0.18 kg of polypropylene fiber, 7 kg of composite powder, and 1.2 kg of yttrium trioxide powder are mixed to obtain the high-strength refractory material.

[0048] Example 6

[0049] Step 1: 1.4 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. in a nitrogen environment for 2 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0050] Step 2: 5.5g of acrylic acid and 2.5g of pure water were mixed in a weight ratio to obtain solution A; 2g of 3-mercaptopropionic acid, 1.5g of L-ascorbic acid, and 60g of pure water were mixed to obtain solution B; 68g of isopentanol polyoxyethylene ether and 4.5g of phosphate monomer were added to 25g of pure water, heated to 60°C, and 0.4g of hydrogen peroxide was added after dissolution. After stirring for 15min, 6.2g of solution A and 6.4g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0051] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.2:1; use sodium hydroxide to maintain the pH of the system to 10, stir and stand for 1 hour, centrifuge and dry to obtain the core powder; take 10g of the core powder and disperse it in 50g of pure water, add 2g of sodium dodecylbenzene sulfonate, stir for 30min, add 17g of calcium chloride solution dropwise, add 22g of sodium carbonate solution after the addition is completed, obtain a suspension, stir and react for 2h, filter, dry, calcine, and grind to obtain a composite powder;

[0052] Step 4: 67 kg of high-alumina aggregate, 22 kg of silicon carbide powder, 8 kg of α-alumina powder, 5 kg of silica particles, 3 kg of silicate cement, 3 kg of spherical asphalt, 2 kg of phosphate-type water reducer, 0.2 kg of polypropylene fiber, 7 kg of composite powder, and 1.5 kg of yttrium trioxide powder are mixed to obtain the high-strength refractory material.

[0053] Comparative Example 1

[0054] Use traditional polycarboxylate water reducer.

[0055] Step 1: 5g of acrylic acid and 2g of pure water are mixed according to a weight ratio to obtain solution A; 1.8g of 3-mercaptopropionic acid, 1.2g of L-ascorbic acid, and 50g of pure water are mixed to obtain solution B; 63g of isopentanol polyoxyethylene ether is added to 20g of pure water, heated to 50°C, and 0.38g of hydrogen peroxide is added after dissolution, and 5.8g of solution A and 6g of solution B are added dropwise at the same time after stirring for 15min, and solution A is added dropwise for 3h, and solution B is added dropwise for 3.5h to obtain a reaction solution; the reaction solution is kept warm for 1.5h, and after the reaction is completed, the temperature is lowered and the pH value is adjusted to 7 to obtain a polycarboxylic acid water reducer;

[0056] Step 2: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr4+ )=1:1; use sodium hydroxide to maintain the pH of the system to 9, stir and stand for 1 hour, centrifuge and dry to obtain the core powder; take 5g of the core powder and disperse it in 30g of pure water, add 1g of sodium dodecylbenzene sulfonate, stir for 30min, add 13g of calcium chloride solution dropwise, add 15g of sodium carbonate solution after the addition is completed, obtain a suspension, stir and react for 1h, filter, dry, calcine, and grind to obtain a composite powder;

[0057] Step 3: 62 kg of high-alumina aggregate, 13 kg of silicon carbide powder, 4 kg of α-alumina powder, 3 kg of silica particles, 2 kg of silicate cement, 2 kg of spherical asphalt, 1 kg of polycarboxylic acid water reducer, 0.1 kg of polypropylene fiber, 3 kg of composite powder, and 0.5 kg of yttrium trioxide powder are mixed to obtain a refractory material.

[0058] Comparative Example 2

[0059] Calcium carbonate particles are used instead of composite powder to prepare refractory materials.

[0060] Step 1: 1.1 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. in a nitrogen environment for 1.5 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0061] Step 2: 5.1g of acrylic acid and 2g of pure water were mixed in a weight ratio to obtain solution A; 1.9g of 3-mercaptopropionic acid, 1.25g of L-ascorbic acid, and 50g of pure water were mixed to obtain solution B; 62g of isopentanol polyoxyethylene ether and 3.75g of phosphate monomer were added to 20g of pure water, heated to 50°C, and 0.36g of hydrogen peroxide was added after dissolution. After stirring for 15min, 5.8g of solution A and 6.3g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0062] Step 3: Mix 63kg of high-alumina aggregate, 15kg of silicon carbide powder, 5kg of α-alumina powder, 3.8kg of silica particles, 2.4kg of silicate cement, 2.1kg of spherical asphalt, 2kg of phosphate-type water reducer, 0.13kg of polypropylene fiber, 3.8kg of calcium carbonate particles, and 0.6kg of yttrium trioxide powder to obtain a refractory material.

[0063] Comparative Example 3

[0064] The calcium carbonate particles and the inner core powder are directly blended to prepare the refractory material.

[0065] Step 1: 1.19 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 10° C. in a nitrogen environment for 1.5 h, filtered, and vacuum dried to obtain a phosphate monomer;

[0066] Step 2: 5.2g of acrylic acid and 2.3g of pure water were mixed in a weight ratio to obtain solution A; 1.86g of 3-mercaptopropionic acid, 1.34g of L-ascorbic acid, and 58g of pure water were mixed to obtain solution B; 65g of isopentanol polyoxyethylene ether and 3.9g of phosphate monomer were added to 22g of pure water, heated to 55°C, and 0.37g of hydrogen peroxide was added after dissolution. After stirring for 15min, 5.94g of solution A and 6.15g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0067] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.05:1; using sodium hydroxide to maintain the pH of the system to 10, stirring and standing for 1 hour, centrifuging and drying to obtain the inner core powder;

[0068] Step 4: Mix 65kg of high-alumina aggregate, 17kg of silicon carbide powder, 6kg of α-alumina powder, 4.9kg of silica particles, 2.5kg of silicate cement, 2.7kg of spherical asphalt, 1.5kg of phosphate ester water reducer, 2.4kg of calcium carbonate particles, 0.1kg of polypropylene fiber, 2.4kg of core powder, and 0.7kg of yttrium trioxide powder to obtain a refractory material.

[0069] Comparative Example 4

[0070] The refractory material is prepared without adding yttrium trioxide.

[0071] Step 1: 1.24 mol of 2-acrylamide-2-methylpropanesulfonic acid and 1 mol of L-2-amino-3-hydroxybutyric acid-3-phosphate are dispersed in a sodium chloride solution, reacted at 15° C. for 2 h in a nitrogen environment, filtered, and vacuum dried to obtain a phosphate monomer;

[0072] Step 2: 5.3g of acrylic acid and 2.28g of pure water were mixed in a weight ratio to obtain solution A; 1.83g of 3-mercaptopropionic acid, 1.41g of L-ascorbic acid, and 50g of pure water were mixed to obtain solution B; 67g of isopentanol polyoxyethylene ether and 4g of phosphate monomer were added to 22g of pure water, heated to 50°C, and 0.39g of hydrogen peroxide was added after dissolution. After stirring for 15min, 6.1g of solution A and 6.23g of solution B were added dropwise at the same time. Solution A was added dropwise for 3h, and solution B was added dropwise for 3.5h to obtain a reaction solution; the reaction solution was kept warm for 1.5h, and after the reaction was completed, the temperature was lowered and the pH value was adjusted to 7 to obtain a phosphate type water reducer;

[0073] Step 3: Mix lanthanum nitrate, zirconium oxychloride and pure water to obtain a precursor solution, wherein n(La 3 + ): n(Zr 4+ )=1.15:1; use sodium hydroxide to maintain the pH of the system to 9.5, stir and stand for 1h, centrifuge and dry to obtain the inner core powder; take 8.7g inner core powder and disperse it in 45g pure water, add 1.6g sodium dodecylbenzene sulfonate, stir for 30min, add 15g calcium chloride solution dropwise, add 20.3g sodium carbonate solution after the addition is complete, obtain a suspension, stir and react for 2h, filter, dry, calcine, and grind to obtain a composite powder;

[0074] Step 4: 66 kg of high-alumina aggregate, 18.6 kg of silicon carbide powder, 7.5 kg of α-alumina powder, 4.3 kg of silica particles, 2.8 kg of silicate cement, 2.8 kg of spherical asphalt, 1.76 kg of phosphate-type water reducer, 0.2 kg of polypropylene fiber, and 5.8 kg of composite powder are mixed to obtain the high-strength refractory material.

[0075] experiment:

[0076] The refractory materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were hardened at 35°C for 3 hours and heat treated at 1400°C for 3 hours to obtain finished products. The finished products of 25cm×10cm×5cm were taken for performance testing, and the experimental results are shown in the following table. Among them:

[0077] Strength test: including room temperature flexural strength and room temperature compressive strength. The room temperature flexural strength test method uses three-point bending equipment for testing; the room temperature compressive strength is tested using a pressure testing machine;

[0078] Stability test: Heat the finished product to 1200℃, cool it to 30℃ with cold water immediately after thermal shock for 10 minutes, cycle for 100 hours, and test the strength retention rate.

[0079] project Room temperature flexural strength / MPa Normal temperature compressive strength / MPa Strength retention Example 1 13.83 108 71% Example 2 13.12 110 70% Example 3 15.21 113 71% Example 4 14.39 111 74% Example 5 13.91 111 73% Example 6 12.42 109 70% Comparative Example 1 11.72 105 / Comparative Example 2 10.13 96 58% Comparative Example 3 10.62 104 55% Comparative Example 4 10.59 99 57%

[0080] in conclusion:

[0081] From the data of Examples 1 to 6 in the above table, it can be seen that the refractory material prepared by the present invention has good high temperature resistance, and the strength retention rate can reach more than 70% after 100h of thermal shock and water cooling, which is suitable for preparing the lining of the incinerator. Comparing Example 1 with Comparative Example 1, Example 1 uses phosphate as a monomer, introduces phosphate groups in the water reducer structure, and produces phosphate groups after hydrolysis, which has a stronger adsorption effect on calcium ions in cement, not only forming a stable structure on the cement surface, but also improving the interface compatibility of each component, so the materials are more uniform after mixing than those in Comparative Example 1, and the strength of the prepared refractory finished product is higher. Comparing Example 2 with Comparative Example 2, the core powder of the composite powder in Example 2 is lanthanum zirconate, and the shell is calcium carbonate; lanthanum zirconate has the advantages of high thermal stability, strong anti-sintering ability, low thermal expansion coefficient, etc., which improves the high temperature resistance and durability of the refractory material; and since lanthanum zirconate is not added in Comparative Example 2, the high temperature resistance is not as good as Example 2, and the mechanical strength of the material has decreased significantly after thermal shock and water cooling cycle treatment. Comparing Example 3 with Comparative Example 3, when the baking temperature increases, the calcium carbonate in Example 3 is thermally decomposed to emit carbon dioxide and calcium oxide, and the carbon dioxide will generate pore space around the lanthanum zirconate; the presence of yttrium trioxide causes the silicon dioxide, magnesium oxide, iron oxide, calcium oxide and other components in the refractory material to form a low eutectic liquid phase during the sintering process, and the liquid phase diffuses into the pore space to form a wrapping around the lanthanum zirconate; lanthanum zirconate has a grain boundary strengthening effect, and the liquid phase directly forms a crystalline phase and then combines with lanthanum zirconate, which effectively reduces the apparent porosity of the refractory material and improves the density, while also improving the problem of poor toughness of lanthanum zirconate, thereby improving the flexural and compressive strength of the refractory material; while in Comparative Example 3, calcium carbonate and lanthanum zirconate are directly blended, and the location of the pores generated after the thermal decomposition of calcium carbonate is more random, and the liquid phase cannot be concentrated around the lanthanum zirconate to form a wrapping structure after diffusion, which is effective in reinforcing the lanthanum zirconate, and ultimately the performance of the refractory material in Comparative Example 3 is not as good as that in Example 3. Comparing Example 4 with Comparative Example 4, yttrium trioxide was not added in Comparative Example 4, and the sintering process was mainly solid-phase reaction; the solid-phase fluidity was poor, and the pores generated after the decomposition of calcium carbonate could not be filled, the apparent porosity was large, and it was difficult to form a high-strength coating layer on its surface, so the performance of the refractory material was poor.

[0082] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength refractory material for an incinerator lining, characterized in that: The following steps are involved: Step 1: Disperse 2-acrylamide-2-methylpropanesulfonic acid and L-2-amino-3-hydroxybutyric acid-3-phosphate in a sodium chloride solution, filter and vacuum dry after the reaction is completed in a nitrogen environment to obtain a phosphate monomer; Step 2: Mix acrylic acid with pure water to obtain solution A; mix 3-mercaptopropionic acid, L-ascorbic acid and pure water to obtain solution B; add isopentanol polyoxyethylene ether and phosphate monomer into pure water, heat to dissolve, add hydrogen peroxide and stir, and simultaneously add solution A and solution B dropwise to obtain a reaction solution; after heat preservation and reaction, adjust the pH value to 6-7 to obtain a phosphate type water reducer; Step 3: lanthanum nitrate, zirconium oxychloride and pure water are mixed to obtain a precursor solution; sodium hydroxide is used to maintain the pH of the system to 9-10 for reaction, centrifugation is performed, and drying is performed to obtain a core powder; the core powder and sodium dodecylbenzene sulfonate are dispersed in pure water, and a calcium chloride solution is added dropwise. After the addition is completed, a sodium carbonate solution is added to obtain a suspension, and a composite powder is obtained by reaction; Step 4: Mix high-alumina aggregate, silicon carbide powder, α-alumina powder, silica particles, silicate cement, spherical asphalt, phosphate-type water reducer, polypropylene fiber, composite powder, and yttrium trioxide powder to obtain the high-strength refractory material.

2. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 1, the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to L-2-amino-3-hydroxybutyric acid-3-phosphate is (1.1-1.4):

1.

3. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 1, the reaction temperature is 5 to 15° C. and the reaction time is 1 to 2 h.

4. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 2, the contents of the components in solution A are, by weight, 5 to 5.5 parts of acrylic acid and 2 to 2.5 parts of pure water.

5. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 2, the contents of the components in solution B are, by weight, 1.8 to 2 parts of 3-mercaptopropionic acid, 1.2 to 1.5 parts of L-ascorbic acid, and 50 to 60 parts of pure water.

6. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 2, the contents of the components in the reaction solution are, by weight, 63 to 68 parts of isopentanol polyoxyethylene ether, 3.7 to 4.5 parts of phosphate monomers, 20 to 25 parts of pure water, 0.36 to 0.4 parts of hydrogen peroxide, 5.8 to 6.2 parts of solution A, and 6 to 6.4 parts of solution B.

7. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 3, in the precursor solution, La 3+ With Zr 4+ The molar ratio is (1~1.2):

1.

8. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 3, the contents of the components in the suspension are, by weight, 5 to 10 parts of core powder, 1 to 2 parts of sodium dodecylbenzene sulfonate, 30 to 50 parts of pure water, 13 to 17 parts of calcium chloride solution, and 15 to 22 parts of sodium carbonate solution.

9. The method for preparing a high-strength refractory material for an incinerator lining according to claim 1, characterized in that: In step 4, the contents of each component in the high-strength refractory material are, by weight, 62 to 67 parts of high-alumina aggregate, 13 to 22 parts of silicon carbide powder, 4 to 8 parts of α-alumina powder, 3 to 5 parts of silica particles, 2 to 3 parts of silicate cement, 2 to 3 parts of spherical asphalt, 1 to 2 parts of phosphate-type water reducer, 0.01 to 0.2 parts of polypropylene fiber, 3 to 7 parts of composite powder, and 0.5 to 1.5 parts of yttrium oxide powder.

10. An incinerator lining prepared by the method for preparing a high-strength refractory material for an incinerator lining according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Water-reducing slump-retaining type polycarboxylic acid water reducing agent and preparing method thereof

    CN105367720A

  • Clay-resisting slow-release slump-retaining type polycarboxylate superplasticizer and preparation method thereof

    CN109626859A